The feasibility study of coffee house business opportunity in COVID-19 pandemic: a case study at kulo coffee shop pemogan - Sudiartini, Ni Wayan Ari; Astari, Anak Agung Elik; Kardini, Ni Luh; Dhani, Yenni Rahman (International research journal of management, IT and social sciences, 2020)
In running a business, there are certainly a lot of things to be aware of. Anything that can affect the company needs to be taken into account. Through the business feasibility study, business owner can be aware of the information regarding current business position. The information is used as a reference for the owner to run the business ahead. Kulo coffee shop Pemogan is currently facing a situation that requires the owner to be more creative and innovative amid similar business competition that is very strict especially in COVID-19 pandemic. This business feasibility study applied quantitative and qualitative data analysis techniques. Data were obtained through interviews, observations, and documentations conducted at the Kulo coffee shop Pemogan. The data obtained from the research object were then immediately collected and processed. The stages conducted in analyzing the feasibility are through aspects such as market and marketing aspects, legal aspects, technical and technological aspects, environmental aspects, and financial aspects. In finding out the business opportunity of Kulo coffee shop Pemogan, SWOT analysis was done. It consisted of strengths, weaknesses, opportunities, and threats of this business.